Degradation of the oxirane ring of epoxidized oleic acid in a liquid catalyzed reaction system - Wibowo, Tri Yogo; Rusmandana, Bayu; astuti, Astuti (Jurnal Teknologi Pertanian, 2013)
Epoxidized oleic acid was produced using acetic acid as a carrier of oxygen in liquid organic media. The attack on the oxirane ring by nucleophilic ion takes place in the epoxidation process with liquid catalyst, so decreased the yield of the epoxy. We report a study of degradation of oxirane ring influenced by the amount of sulfuric acid catalyst and addition time of hexane on the epoxidation reaction of oleic acid with hydrogen peroxide. The results show that increasing amount of sulfuric acid catalyst not only can increase rate of reaction but also can affect degradation of epoxide increased. On the process conditions: temperature of 50-55 ÂºC; mole ratio of oleic acid: acetic acid: hydrogen peroxide = 1 : 0.4 : 1.5; and stirrer speed of 1200 rpm, the amount obtained by sulfuric acid catalyst is best at 3.5% which can result in a number epoksid oxirane and iodine numbers are 3.15 and 4.66, respectively. Meanwhile, the hexane addition did not influence on the reaction rate of double bond cleavage, however the hexane addition at the right time can decrease the degradation of oxirane ring. The addition of a 125 g hexane at the first hour gave the degradation oxirane low at 50%. Keywords: oleic acid, epoxide, oxirane ring, degradation